(untitled) (Samriddhi Journal of Development Studies, 2025)
This paper outlines Baji’s (Chiura/beaten rice) role in the Newar tradition. The study, applying cultural ecological theory with a constructivism paradigm, examines what and how Baji plays a cultural value-based role among the Newar community of Bhaktapur. The study focuses on the uses of Baji in traditional festivals, rites and rituals in particular and in daily life of the Newar community in general. Baji is a food item in different Nepali communities; however, it is more than a food item in the Newar community. Representing a deep rooted cultural tradition in the Newar community, it brings the members of the Newar community together. Baji is one of the key social connecting factors and items of cultural identity among Newar as a symbol of unity. The study reviews relevant literature availed published and unpublished. Culture experts and stakeholders were interviewed as key informants for primary data. This study explores that Baji is an absolutely necessary item in rituals from births to death, festivals or similar occasions. This study shade lights how the Baji maintains its identity in modern times while still holding deep meaning for the Newar community.